Some Peculiarities of Expressing the Category of Emotivity - Nigina Mahmudovna, Muhammadieva (Indonesian Journal of Innovation Studies, 2022)
The article discusses some peculiarities of expressing the meaning of emotivity. It also deals with the works of famous linguists.